2012
DOI: 10.1161/circresaha.112.266445
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ROMK Channel Is a Molecular Component of MitoK ATP

Abstract: Rationale Activation of the mitochondrial ATP-sensitive potassium channel (mitoKATP) has been implicated in the mechanism of cardiac ischemic preconditioning, yet its molecular composition is unknown. Objective To use an unbiased proteomic analysis of the mitochondrial inner membrane to identify the mitochondrial K+ channel underlying mitoKATP. Methods and Results Mass spectrometric analysis was used to identify KCNJ1(ROMK) in purified bovine heart mitochondrial inner membrane and confirmed that ROMK mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
159
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(174 citation statements)
references
References 54 publications
(57 reference statements)
10
159
2
3
Order By: Relevance
“…Pharmacological evidence, using the classical mitoK ATP channel agents diazoxide and 5-HD, would suggest that mitoK ATP channels do indeed play a role; however the specificity of these agents has been called into question [23]. The recent identification of ROMK as a putative mitoK ATP channel subunit [24] provides a potential target for further investigation. Additionally, the role of sarcoK ATP channels in cardioprotection may be as part of a larger signalasome-type complex [40].…”
Section: Evidence For a Role Of Sarcok Atp Channel Subunits In Cardiomentioning
confidence: 99%
“…Pharmacological evidence, using the classical mitoK ATP channel agents diazoxide and 5-HD, would suggest that mitoK ATP channels do indeed play a role; however the specificity of these agents has been called into question [23]. The recent identification of ROMK as a putative mitoK ATP channel subunit [24] provides a potential target for further investigation. Additionally, the role of sarcoK ATP channels in cardioprotection may be as part of a larger signalasome-type complex [40].…”
Section: Evidence For a Role Of Sarcok Atp Channel Subunits In Cardiomentioning
confidence: 99%
“…Using an electrophysiological approach, we ruled out the presence of any other cation-selective channel activity in our F1Fo preparations (Figure 1 -figure supplement 2A,B). It has been suggested that a mitochondrial ROMK potassium channel might act as the pore-forming subunit of a cytoprotective mKATP channel (Foster et al, 2012). Our immunoblotting with anti-ROMK antibody ruled out ROMK channel contamination of the isolated F1Fo (Figure 1 -figure supplement 2C).…”
Section: Potassiummentioning
confidence: 64%
“…Nature usually operates important pathways with built-in redundancy so that other mitochondrial K + channels may contribute to these mechanisms, including the Ca 2+ -activated K + channel, BKCa (Xu et al, 2002), and a ROMK channel which may also mimic mKATP channel function (Foster et al, 2012), but these pathways are likely fine-tuning mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Diazoxide does not elicit sK ATP channel current in ventricular myocytes, and its protective benefits require the presence of the K ATP channel subunit SUR1 and may involve inhibition of succinate dehydrogenase (15,18,19). Activity at a proposed mitochondrial K ATP channel is supported only by indirect methods and no mitochondrial K ATP channel has been identified at the molecular level or cloned (23,24). Similarly, efforts to localize known K ATP subunits in mitochondria have been inconsistent and controversial (25,26).…”
Section: Discussionmentioning
confidence: 99%